Freestyle swimming: An insight into propulsive and resistive mechanisms - Honda, K.; Keys, M.; Lyttle, A.; Alderson, J.; Bennamoun, M.; El-Sallam, A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The mechanisms behind propulsion and drag generation in swimming have proven difficult to accurately and comprehensively measure. With fluid effects being the major contributing factor for swimming performance, the ability to accurately determine these effects is of great importance. Computational Fluid Dynamics (CFD) modelling provides a solution to this problem. CFD can not only quantify the net effect of the forces acting on a swimmer, but also that observed at each individual segment. CFD modelling allows complex fluid flow regimes and geometry to be simulated. The results of a CFD analysis allowed for the distribution of the forces across the body throughout the freestyle stroke to be examined. The results of this analysis include an increased level of foundational knowledge with applied outcomes that may be used to improve swimming performance.